BRANCHING OUT: A CASE STUDY OF TEEAL UTILIZATION AT NCAM LIBRARY FOR AGRICULTURAL INSIGHTS - Babatunde, Adekunle Olufemi (Current Journal of Library and Information Sciences (CJLIS), 2023)
The Essential Electronic Agricultural Library (TEEAL) is a dynamic and comprehensive research resource, offering access to over 450 high-quality research journals in agriculture and related sciences. Launched in 1999, TEEAL boasts a vast repository of full-text, searchable articles and graphics drawn from more than 200 major agricultural journals. This resource is a collaborative project spearheaded by Cornell University's Albert R. Mann Library, with the support and cooperation of more than 60 influential scientific publishers, societies, and index providers. Its establishment was made possible through the initial financial backing of the Rockefeller Foundation, with ongoing support from various foundations and donors. The concept of TEEAL emerged in the 1980s and was conceived by Wallace Olsen, former Senior Research Associate, and Jan Olsen, former Director of Mann Library. The motivation for TEEAL arose from their experiences during travels to developing countries, where they encountered underfunded and outdated journal collections. Recognizing the critical role of up-to-date research in advancing food security and agricultural development, TEEAL was conceived as a means to empower scientists with enhanced access to current research. This paper explores the origins and development of TEEAL, shedding light on its evolution from a visionary idea into a powerful tool for improving food security and agricultural progress. The collaboration with scientific publishers, societies, and index providers is a testament to the importance of TEEAL's mission and its broader implications for the global scientific community.